Knowledge Production and Contradictory Functions in African Higher Education - Bailey, Tracy; Maassen, Peter A. M.; Cloete, Nico (African minds higher education dynamics series ;, 2015)
The dominant global discourse in higher education now focuses on 'world-class' universities - inevitably located predominantly in North America, Europe and, increasingly, East Asia. The rest of the world, including Africa, is left to play 'catch-up'. But that discourse should focus rather on the tensions, even contradictions, between 'excellence' and 'engagement' with which all universities must grapple. Here the African experience has much to offer the high-participation and generously resourced systems of the so-called 'developed' world. This book offers a critical review of that experience, and so makes a major contribution to our understanding of higher education.